Synthesis and antioxidant study of new hydrazones derived from bisdemethoxycurcumin pyrazole - Alsalim, Tahseen Abdul Qader; Mzban, Hussain Ali; Abood, Einas Nasir (European Journal of Chemistry, 2017)
The antioxidant activity of new hydrazones derived from bisdemethoxycurcumin pyrazole was investigated. The study was divided into two main parts: The first one includes the synthesis and characterization of the target compounds from bisdemethoxycurcumin (BDMC), while the second step is devoted to the investigation of their antioxidant activities. In the first step of synthesis, the curcumin-pyrazole (2) was synthesized by the reaction of BDMC with hydrazine hydrate. Later, the obtained product treated with ethyl 2-chloroacetate to produce curcumine ester (3), then the product was converted to hydrazide (4) by the reaction of curcumin ester (3) with hydrazine hydrate. Finally, curcumine hydrazones (5a-f) were synthesized from the reaction of hydrazide (4) with substituted aromatic aldehydes. All compounds were characterized with the aid of suitable spectroscopic techniques. The antioxidant activity of the prepared compounds was studied against the stable radical α,α-diphenyl-β-picrylhydrazyl. The study showed that only the phenolic OH-containing compounds (2, 5b and 5f) have antioxidant activity.